Merging gold plasmonic nanoparticles and l-proline inside a MOF for plasmon-induced visible light chiral organocatalysis at low temperature; Nanoscale; Vol. 16, iss. 10 - Kushnarenko A, S, Angelina Sergeevna; Zabelina A. A. Anastasiya Aleksandrovna; Guselnikova O. A. Olga Andreevna; Milyutina (Miliutina) E. V. Elena Vadimovna; Vokata B.; Zabelin D, V, Denis Vladimirovich; Burtsev V.; Valiev R. R. Rashid Rinatovich; Kolska Zd. Zdenka; Paidar M.; Sikora V, Yu. Vadim Yurjevich; Postnikov P. S. Pavel Sergeevich; et al. (2024, 2024)
Title screen